Mammary carcinoma in a mixed tumor with myeloid metaplasia component presenting Leishmania spp. in a dog - Arenales, Alexandre; Ferreira, Jefferson; Almeida, Ana Carolina O.; Rozza, Daniella B.; Luvizotto, Maria Cecília R. (Brazilian Journal of Veterinary Pathology, 2020)
Here is described a 9-years-old, intact female dog with cytopathological analysis from mammary tumors containing Leishmania spp. amastigotes in macrophages. The animal was submitted to euthanasia and necropsy was performed. Histopathological diagnosis was a mammary carcinoma in a mixed tumor, grade I, with myeloid metaplasia component containing macrophages laden with a large amount of amastigotes. For confirmation, immunohistochemistry was used in neoplastic tissue and resulted in strong positivity for Leishmania antibody. Myeloid metaplasia portion of mammary carcinoma in a mixed tumor may be, rarely, a site for diagnosis of Canine Visceral Leishmaniasis.